The Pumpkin Spice Café / Laurie Gilmore. - Gilmore, Laurie (Dream Harbor series ;, 2023)
Jeanie is more surprised than anyone when her aunt bequeaths her the quaint Pumpkin Spice Café. Especially since her aunt isn't dead, she's alive and well, and currently off working on her tan. Jeanie could have said no. And the old Jeanie would have. But now she's determined to be the sunshiney owner of the town's only coffee shop. Logan is not usually one to care about town gossip. In fact, he avoids it at all costs. All he wants is to drop off his produce to the local businesses and then return to the farm he runs with his grandparents. But there are strange things happening in the café, odd noises and misplaced items and lights on the fritz. And Jeanie needs Logan's help. But Logan wants nothing to do with the pretty new girl who probably won't stick around, it's just a shame he can't stop thinking about her.